Fake Diplomas, Real Consequences: Legal and Ethical Challenges in the Legal Profession - Sistyawan, Dwanda Julisa; Neonbeni, Randy Vallentino; Rizal, Muhamad; Kusuma, Ariska Cesar Divian Candra; Husain, Husain (Constitutionale, 2024)
Integrity and trust are fundamental in the legal profession, yet diploma forgery threatens these values, leading to ethical violations and diminished public trust. This study examines the legal implications of diploma forgery in Case No. 20/Pid.B/2024/PN Tmg, where an individual used a fraudulent diploma to practice law. Using a normative legal approach, the study analyzes court decisions, legal doctrines, and statutory regulations, including Article 263 of the Indonesian Penal Code and Article 69 of Law No. 20 of 2003. Findings reveal weaknesses in verification systems, allowing unqualified individuals to enter the legal profession. To prevent such fraud, the study proposes blockchain-based diploma verification, offering tamper-proof credentialing and real-time authentication. Stricter regulations, enhanced verification, and ethical awareness campaigns are crucial to safeguarding legal integrity. Adopting blockchain verification can restore public trust, ensure professional accountability, and uphold the credibility of legal institutions.